Phonetic system and sign formation when Ferdinand de Saussure (Journal of the College of Basic Education, 2022)
The research displays read sayings the Saussure approach that tried to disengagement and the overlap between the ideas and sounds in the light of the epistemic approach and thinker Syoussologi vision tongue Association specific aspects of the relationship between both sides of the tag elements and language present (Signifiers), and missing elements (Signifieds). .. Deals with foundations that represent determinants of systematic circuit systems audio languages​​, standing at some discrepancy conceptual between categories Saussure that need reflection and a new reading such as abstraction, which is dictated by the Saiklogih event language and its associated foundations of the theory, such as arbitrary, and what was the relationship between language and the system when Ferdinand de Saussure relationship concerted of marks in the form of System complex van his statements focused on the study of the sign unit through the analysis of pivot tools systematically diagnosed relations, internal speaker system or mark which is termed in syntagme correlation which gives the elements of unity spoken worth Fine through interaction career between those elements in under synchronous present.